Penerapan Model Teams Games Tournament (TGT) Berbantuan Media Ular Tangga pada Materi Perubahan Wujud Benda untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Inpres Naikoten 2 - Helena Maria Be Bunga An; Lolang Maria Masi; Netty Elisabeth Antonetha Nawa (ARZUSIN, 2025)
The low learning outcomes of fourth-grade students at SD Inpres Naikoten 2 on the topic of changes in the state of matter in science lessons serve as the background of this study. One contributing factor is the continued use of conventional teaching methods, which result in low student engagement in the learning process. This research aims to evaluate the impact of implementing the Teams Games Tournament (TGT) learning model integrated with the snakes and ladders game as an educational medium to improve student learning outcomes. The study employed a Classroom Action Research approach involving 19 students (7 boys and 12 girls). Data collection techniques included observation of teacher and student activities, evaluation of learning outcomes, and instructional documentation. Data were analyzed both qualitatively and quantitatively. Prior to the implementation of the TGT model, the student mastery percentage was only 36.84%. After the first cycle, mastery increased to 57.89%, with average teacher activity observation scores at 78.75 and student activity at 72.5. Improvements in the second cycle resulted in a significant increase, with student mastery reaching 89.47%, and teacher and student activity scores at 95 and 98.03, respectively. These findings demonstrate that the TGT model, supported by the snakes and ladders game, fosters an active, competitive, and enjoyable learning environment, thereby positively impacting student achievement. The study implies that integrating the cooperative TGT model with educational games is an innovative and effective strategy for teaching science in elementary schools.